A biomass approach to mendable bio-elastomers. Issue 6 (23rd January 2017) - Yuan, Liang; Wang, Zhongkai; Ganewatta, Mitra S.; Rahman, Md Anisur; Lamm, Meghan E.; Tang, Chuanbing
Abstract : Sustainable bioelastomers with high elastic recovery, high resilience and mendability are conceptualized with low chain-entanglement polymers that are predominantly originated from renewable biomass. Abstract : Sustainable bioelastomers with high elastic recovery, high resilience and mendability are conceptualized with low chain-entanglement polymers that are predominantly originated from renewable biomass. Polymers with plant oil-derived fatty groups at the side chain were installed with furan, which allowed Diels–Alder addition to introduce dynamic covalent crosslinking. These elastomers are mendable via retro Diels–Alder. Reprocessing of these polymers led to the formation of elastomers with preservation of excellent resilience and elastic recovery.